Spatial Frequency Integration During Active Perception: Perceptual Hysteresis When an Object Recedes - Brady, Timothy; Oliva, Aude (Frontiers in Psychology, 2012)
As we move through the world, information about objects moves to different spatial frequencies. How the visual system successfully integrates information across these changes to form a coherent percept is thus an important open question. Here we investigate such integration using hybrid faces, which contain different images in low and high spatial frequencies. Observers judged how similar a hybrid was to each of its component images while walking towards or away from it or having the stimulus moved towards or away from them. We find that when the stimulus is approaching, observers act as if they are integrating across spatial frequency separately at each moment. However, when the stimulus is receding, observers show a perceptual hysteresis effect, holding on to details that are imperceptible in a static stimulus condition. Thus, observers appear to make optimal inferences by sticking with their previous interpretation when losing information but constantly reinterpreting their input when gaining new information.